Debridement, internal fixation and staged autogenous bone graft for the management of infected femoral non-union. (December 2018) - Pace, F.; Randelli, F.; Ayeni, O.R.; Pace, A.
Abstract: An infected non-union is a major and potentially devastating complication following bone fractures. It is often debilitating for the patients, physically and psychologically, because of its long healing period and emotional toll on patient and caregivers. Different surgical procedures (in one or two stages) are described in literature for its treatment. These range from external fixation (axial or circular) to internal fixation (nails or plates) associated or not with different types of biological support/augmentation (iliac crest bone graft, platelet rich plasma, bone morphogenic protein, etc.). This case report is about a 19 y.o. man affected by an infected non-union of the femoral shaft, who had to undergo a revision surgery a year after his accident. The treatment chosen by the senior author was the following one stage procedure: external fixator removal, surgical debridement, reduction and fixation of the fracture with a locked plate (internal fixator), bone graft and antibiotic cement usage. The use of new iliac crest bone graft after three months was necessary to obtain radiographic and clinical healing with great patient's satisfaction. The autologous iliac bone graft was chosen because it was necessary to give the patient the highest chance of healing. Despite the great experimental and clinical efforts to stimulate the biological healing process through the use of growth factors, stem cells, tissue scaffolds and other methods, today the gold standard of bone graft is still the autologous cancellous bone from the iliac crest.